Hypoxia in patients with acute hemiplegia. Issue 6410 (7th January 1984) - Walshaw, M J; Pearson, M G
Abstract : Sixteen patients with an early dense hemiplegia due to cerebrovascular accidents were shown to have a greater degree of hypoxia than 16 matched control patients. The patients with hemiplegia had a reflex compensatory fall in arterial carbon dioxide tensions (PaCO2) with possible reduction in cerebral blood flow. Oxygen treatment led to an increase in PaCO2 in the patients with hemiplegia, but the increase in oxygen tensions in these patients was significantly less than that in the control group, suggesting increased pulmonary shunting as the cause for the hypoxia. Oxygen treatment may improve cerebral blood flow and oxygenation and have a useful role in the early management of patients with a dense hemiplegia.